Market Analysis and Consumer Behavior of Indomaret Minimarkets in Banjarmasin City - Mohdari; Fahmi, Muhammad; Safitri, Novia Angga; Syafril (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of the modern Indomaret minimarket cannot be separated from changes in consumer shopping behavior who want to be fast and do not like the process of haggling over prices like shopping at traditional markets. This research aims to conduct market analysis and consumer behavior at the Indomaret Minimarket in Banjarmasin City. This research is very useful for economic development and policy making in the Banjarmasin City government. This research is a qualitative descriptive research using literature study methods and observation of the objects studied. Data collection was carried out by studying the literature and making direct observations at the Indomaret minimarket in Banjarmasin City. The results of this research show that the consumer market potential is still very large and widely open to investors and traders. Consumer behavior at the Indomaret minimarket in Banjarmasin City is influenced by several dominant factors such as socio-cultural factors, lifestyle, personality and finances. This research is expected to make a positive contribution to the business world and government.